The effects of interlining types on sewing needle heating - (:unkn) unknown (Fiber Society, 2014)
In this study, a heavy weighted wool fabric was fused by five different types of interlinings. Sewing process was carried out at a constant speed. During the sewing process, the heating rate of the needle was measured. The effects of various interlining types fused to woolen fabric onto the needle heating were investigated.
Keywords: Interlining; Needle heating; Sewing needle; Wool fabric